Effect of Dietary Supplementation of Indigenously Prepared Rumen Protected Fat on Production and Reproduction in Hardhenu Cattle - Sajjan Sihag; Sushil Kumar; Zile Singh Sihag (Indian Journal of Animal Nutrition, 2022)
Dietary fats are important source of energy but unprocessed fat in excess to 6-7% of dry matter intake can reduce ruminal digestion. While, dietary fat in protected form increases energy density of ruminant ration with no negative effects on ruminal fermentation. Rumen protected fat was prepared as calcium salts of long chain fatty acids by an indigenous fusion method. Twelve early lactating Hardhenu cows of 2nd and 3rd parity and average body weight of 408±9.13 kg, yielding 15±0.32 kg milk per day and 15-23 days in milk were subjected either to a control diet (T1) or diet supplemented with indigenously prepared rumen protected fat @ 200g per day per cattle (T2) as per ICAR (2013) feeding standards. Digestibility of dry matter, ether extract and organic matter and intake of total digestible nutrients, digestible ether extract and digestible organic matter improved significantly (P<0.05) in cows fed rumen protected fat (T2). Milk yield, 4% fat corrected milk yield, solid corrected milk yield and fat content of milk were also significantly (P<0.05) increased in T2. Dietary supplementation of rumen protected fat showed positive effect on reproductive performance of cows. Feed conversion efficiency improved in terms of 4% fat corrected milk production in cattle on feeding rumen protected fat and net return was increased by 22.02 % during four months of early lactation.